Judgment [compact disc, unabridged] : a novel - Finder, Joseph (Penguin Audio, 2019)
It was nothing more than a one-night stand. Juliana Brody, a judge in the Superior Court of Massachusetts, is rumored to be in consideration for the federal circuit, maybe someday the highest court in the land. At a conference in a Chicago hotel, she meets a gentle, vulnerable man and in a moment of weakness has an unforgettable night with him. They part with an explicit understanding that this must never happen again. But back home in Boston, it becomes clear that this was no random encounter. Strings are being pulled in high places, a terrifying unfolding conspiracy that will turn her life upside down.